2014
DOI: 10.1038/srep05947
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute CLIP-Seq reveals miRNA targetome diversity across tissue types

Abstract: To date, analyses of individual targets have provided evidence of a miRNA targetome that extends beyond the boundaries of messenger RNAs (mRNAs) and can involve non-Watson-Crick base pairing in the miRNA seed region. Here we report our findings from analyzing 34 Argonaute HITS-CLIP datasets from several human and mouse cell types. Investigation of the architectural (i.e. bulge vs. contiguous pairs) and sequence (Watson-Crick vs. G:U pairs) preferences for human and mouse miRNAs revealed that many heteroduplexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 77 publications
2
68
0
Order By: Relevance
“…This region, usually nucleotides 2–7, forms Watson–Crick (WC) pairs with the target mRNA 3’ untranslated region (UTR) [8, 10]. miRNAs have also been found to target the 5’UTR and coding sequence of the mRNAs as well as pseudogenes and lncRNAs [1114]. Animal miRNAs post-transcriptionally repress target gene expression via transcript degradation and/or translation inhibition [15, 16].…”
Section: The Microrna Sponge Cerna Hypothesis and Its Generalizationmentioning
confidence: 99%
“…This region, usually nucleotides 2–7, forms Watson–Crick (WC) pairs with the target mRNA 3’ untranslated region (UTR) [8, 10]. miRNAs have also been found to target the 5’UTR and coding sequence of the mRNAs as well as pseudogenes and lncRNAs [1114]. Animal miRNAs post-transcriptionally repress target gene expression via transcript degradation and/or translation inhibition [15, 16].…”
Section: The Microrna Sponge Cerna Hypothesis and Its Generalizationmentioning
confidence: 99%
“…Another comprehensive analysis of 34 Argonaute HITS-CLIP datasets from human and mouse cells revealed that many heteroduplexes are "non-canonical" i.e. their seed region comprises G:U and bulge combinations (Clark et al, 2014).…”
Section: Immunoprecipitation Of Small Rna:target Rna Complexesmentioning
confidence: 99%
“…CLIP strategies are nowadays popular for high-throughput analysis of physiological miRNA targets (Chi et al, 2009;Hafner et al, 2010;Leung et al, 2011;Chi et al, 2012;Clark et al, 2014;Grosswendt et al, 2014;Haecker and Renne, 2014;Liu et al, 2014a;Imig et al, 2015) and it is accompanied with a number of algorithms and databases facilitating identification of miRNA targets in high-throughput CLIP data (Hsieh and Wang, 2011;Yang et al, 2011;Balaga et www.efsa.europa.eu/publications 254 EFSA Supporting publication 2017:EN-1246…”
Section: Immunoprecipitation Of Small Rna:target Rna Complexesmentioning
confidence: 99%
“…S9), and we used this information together with MRE conservation and length to prioritize the assignment of a single expressed miRNA to each AGO2 binding site where there was ambiguity due to multiple possible MREs (see Methods for further details). Since miRNAs also target genes in a "noncanonical" manner, through bulges and G:U pairs in the seed region (Chi et al 2012;Helwak et al 2013;Clark et al 2014), and given our novel findings of an increased association between let-7 and AGO2 following DNA damage, we wished to complement our analysis by taking into account potential noncanonical interactions between let-7 and their gene targets on AGO2. To achieve this, we used the miRNA-mRNA interaction data from Clark and coworkers (available at https://cm.jefferson.…”
Section: Par-clip-seq Identifies the Mrna Targets Of Those Mirnas Modmentioning
confidence: 99%
“…To achieve this, we used the miRNA-mRNA interaction data from Clark and coworkers (available at https://cm.jefferson. edu/clip_2014/) that contains HITS-CLIP results from multiple cell lines (Clark et al 2014), focusing on let-7 interactions and selecting those that overlapped with our AGO2 binding sites (Supplemental Table S5). Finally, based on the analysis of AGO2 binding sites and their assignment to targeting miRNAs, we built a comprehensive miRNA-mRNA interaction network (Supplemental Fig.…”
Section: Par-clip-seq Identifies the Mrna Targets Of Those Mirnas Modmentioning
confidence: 99%